2006
DOI: 10.2337/db06-0376
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Insulin-Evoked Responses in Brain Networks Controlling Appetite and Reward in Insulin Resistance

Abstract: The rising prevalence of obesity and type 2 diabetes is a global challenge. A possible mechanism linking insulin resistance and weight gain would be attenuation of insulin-evoked responses in brain areas relevant to eating in systemic insulin resistance. We measured brain glucose metabolism, using [(18)F]fluorodeoxyglucose positron emission tomography, in seven insulin-sensitive (homeostasis model assessment of insulin resistance [HOMA-IR] = 1.3) and seven insulin-resistant (HOMA-IR = 6.3) men, during suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 39 publications
(39 reference statements)
7
147
1
3
Order By: Relevance
“…A blunted sympathetic response may result from impaired insulin transport across the blood-brain barrier, which has been shown in experimentally induced insulin resistance in dogs [41], and from lower cerebrospinal fluid insulin levels, as reported in obese insulin-resistant humans [42]. In line with this, brain insulin resistance coexists with peripheral insulin resistance [43,44].…”
Section: Effects Of Insulin On Vagosympathetic Activitysupporting
confidence: 52%
“…A blunted sympathetic response may result from impaired insulin transport across the blood-brain barrier, which has been shown in experimentally induced insulin resistance in dogs [41], and from lower cerebrospinal fluid insulin levels, as reported in obese insulin-resistant humans [42]. In line with this, brain insulin resistance coexists with peripheral insulin resistance [43,44].…”
Section: Effects Of Insulin On Vagosympathetic Activitysupporting
confidence: 52%
“…Although it would be premature to attempt to pinpoint key sites of insulin resistance in the complex central nervous orchestration of food intake regulation and energy homeostasis, the present data suggest that, besides impaired BBB transport of insulin [4,29,30], which can be overridden by intranasal administration of the hormone, insulin resistance of relevant brain regions may contribute to the pathophysiology of obesity and to its persistence despite chronically elevated circulating insulin concentrations. A recent study in humans [39] using positron emission topography found markedly attenuated brain responses to insulin infusion in patients with insulin resistance in the body periphery. Thus, central nervous insulin resistance may not only be relevant in obesity as such, but may particularly affect diabetic patients with reduced peripheral insulin sensitivity, who would probably benefit specifically from new, central nervous approaches to treatment of this disease.…”
Section: Central Nervous Insulin Resistancementioning
confidence: 99%
“…Thus intranasal insulin administration to increase central nervous availability of the hormone, although apparently ineffective in reducing body weight in the obese state [18], reduces HPA axis activity [18,20,25] and may thus counteract the development of visceral obesity, as well as cognitive impairments assumed to be promoted by excessive HPA axis secretion related to chronic stress. Likewise, boosting hypothalamic insulin signalling may help normalise dysregulated hepatic gluconeogenesis [7], a hallmark of type 2 diabetes and peripheral insulin resistance [34], which appears to be highly associated with central nervous insulin resistance [39]. Conceivably, intranasal insulin could also have some impact on weight regulatory mechanisms after successful weight loss has been achieved (e.g.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…25 Moreover, it seems that insulin resistance in the brain co-occur with insulin resistance in the periphery. 26 Thus, considering the role of insulin in energy balance control, it has been suggested that the natural defense against excessive weight gain through adiposity signalling can be undermined by acquired resistance to adiposity-regulating hormones. 1 This study includes several strengths, including its relatively large sample size and the availability of body composition data instead of simply weight or BMI to estimate adiposity gain, yet, we acknowledge several limitations.…”
Section: Discussionmentioning
confidence: 99%